NAIVITÄT ALS KRITIK - Christian FERENCZ-FLATZ (Studia Universitatis Babeș-Bolyai. Philosophia)
Naiveté as Critique. The present paper addresses the similarities between the concept of “critique” used in phenomenology and the one put forth by critical theory in analyzing their corresponding understanding of “naiveté”. While Husserl develops a broad concept of naiveté in his reflections regarding the phenomenological reduction, where he characterizes the natural attitude as such as “transcendentally naive”, this concept becomes more nuanced when considering the unavoidable naivetés of phenomenology itself, on the one hand, and the complications brought to the mutual relationship between naiveté and critique with his turn towards the life-world. This turn, the paper shows, can be seen as a metacritical reinvestment of naiveté that can also be traced in the works of Adorno.